A training program to extend the reach of the deciphering developmental disorders in Africa (DDD-Africa) study - Charles, Aaliah; Lombard, Zané; Carstens, Nadia; Goliath, Zandisiwe; Lumaka, Aimé; Makay, Prince; Louw, Nadja; Kerr, Robyn; Govender, Daniesha; Krause, Amanda; Devriendt, Koenraad (Frontiers in Genetics, 2025)
Developmental disorders (DD), including intellectual disability (ID) and birth defects, affect approximately 7% of individuals worldwide, contributing to high mortality and lifelong morbidity. These disorders impose significant financial and psychological burdens on affected families. Genetic causes are identified in over 40% of DD cases, but diagnostic challenges, lack of appropriate management and curative treatments, and limited knowledge of natural history complicate management. Genetic testing, such as exome sequencing, is the standard diagnostic approach in developed countries. However, access to genetics services in low- and middle-income countries remains limited. Key barriers include poor access to specialist services in general, limited infrastructure, insufficient expertise in medical genetics, and outdated medical training curricula. The Deciphering Developmental Disorders in Africa (DDD-Africa) international training program initiative aims to address some of these disparities by establishing a network of trained professionals across African countries. This network will drive genomic research by identifying patients with DD, assessing them appropriately to direct genomic testing, and providing support to affected families. The training program consists of three phases: (1) an online course covering training in current core medical genetics concepts, (2) a 2-week on-site practical training in Johannesburg in identification, clinical assessment, and variant interpretation of DD patients, and (3) a hands-on implementation of the complete diagnostic process with four families recruited at each team’s home institute. The program trains healthcare professionals consisting of a clinician and laboratory scientist together, emphasizing the need for collaboration and a comprehensive understanding of integrated genetic clinical assessment and laboratory diagnostics. Ultimately, the initiative seeks to enhance diagnostic capabilities and family support, fostering a strong pan-African network in the field of DD.